PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GIMKIT PADA MATA PELAJARAN METAL INERT GAS (MIG) KELAS XI TEKNIK PENGELASAN SMK NEGERI 1 SUMBAR - M. Hafifurrezy; Bulkia Rahim; Jasman Jasman; Eko Indrawan (Unversitas Negeri Padang, 2024)
Effective learning strategies are needed to improve student learning activities. One approach that can be used by teachers is the use of innovative learning media such as Gimkit. The purpose of this research is to create a Gimkit-based learning media for Metal Inert Gas topic that is valid, practical, and effective. R&D (Research and Development) is the chosen method, and the IDI development model consists of three stages: defining, developing, and evaluating. The results of validation conducted by expert lecturers and subject teachers show that this learning media has a very high validity value in terms of material/content, media, and language. Teachers received a score of 92.5% in the practicality test, placing it in the very practical category. In addition, better learning outcomes after using Gimkit were demonstrated, with an average pretest score of 77 and an average posttest score of 82 respectively. In conclusion, the developed Gimkit-based learning media is valid, practical, and effective, making it suitable to be used as a tool that supports learning.